Mechanistic insights into allosteric structure-function relationships at the M1 muscarinic acetylcholine receptor - Abdul-Ridha, Alaa; Lane, J. Robert; Mistry, Shailesh N.; Lopez, Laura; Sexton, Patrick M.; Scammells, Peter J.; Christopoulos, Arthur; Canals, Meritxell (American Society for Biochemistry and Molecular Biology, 2014)
Background: Selective and potent positive allosteric modulators (PAMs) of the M1 mAChR have been recently described. Results: Use of structural analogues and mutagenic mapping identified the mechanistic basis for increased PAM activity. Conclusion: Combined analytical, structure-function, and modeling approaches uncover allosteric mechanisms at the M1 mAChR. Significance: New chemical space can be explored in the development of tailored M1 mAChR PAMs.